Potensi Astaxantin Topikal dan Oral dalam Menghambat Proses Skin Aging - Wilianto Wilianto; Ni Made Linawati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Indonesia is an archipelagic country located in an area crossed by the equator and only knows the summer and rainy seasons. Between these seasons there is a transition season. Throughout the year Indonesia experiences the heat of the sun and on some islands the exposure to sunlight is greater. This can accelerate the process of skin aging or skin aging which is usually characterized by wrinkles, the appearance of black spots or lentigo, the skin becomes dry and other signs.